The Role of the Fetal MRI to Predict the Postnatal Survival in Fetuses with Congenital Diaphragmatic Hernia - Fatma Ceren Sarioglu; Orkun Sarioglu; Inci Turkan Yilmaz; Bahar Konuralp Atakul; Deniz Oztekin; Ozgur Oztekin (Galenos Publishing House, 2021)
Objective: To assess the role of the magnetic resonance imaging (MRI) to predict the postnatal survival in patients with congenital diaphragmatic hernia (CDH). Method: 25 patients with CDH who had fetal MRI between 2015 and 2020 were enrolled in this retrospective study. Patients were divided into two groups according to the postnatal survival at 30 days of age: alive and dead. The fetal MRI images were assessed to calculate the lung-to-liver signal intensity ratio (LLSIR), and the total lung volume (TLV). In addition, the site of the defect (right or left), accompanying liver herniation (present or absent), detectable-ipsilateral lung parenchyma at the apex (present or absent) were also recorded. MRI images were evaluated by two pediatric radiologists. A p value lesser than 0.05 was considered statistically significant. Results: Among 25 fetuses, 6 were alive and 19 were dead within 30 days after birth. The detectable lung parenchyma had a relationship with the alive group (p = 0.023). Observed-to-expected TLV (p = 0.001) and LLSIR (p = 0.023) were significantly lower in the dead group. Using the cutoff values for the observed-to-expected TLV as 0.27 (a sensitivity of 84%, a specificity of 84%) and for the LLSIR as 2.02 (a sensitivity of 89%, a specificity of 67%) were found as predictors for death. Conclusion: The postnatal survival in CDH may be predicted using the observed-to-expected TLV and LLSIR on the fetal MRI. The presence of the detectable-ipsilateral lung parenchyma at the apex may also be associated with the postnatal survival.